2017
DOI: 10.1136/bmjopen-2016-013810
|View full text |Cite
|
Sign up to set email alerts
|

Screening for seemingly healthy newborns with congenital cytomegalovirus infection by quantitative real-time polymerase chain reaction using newborn urine: an observational study

Abstract: ObjectiveApproximately 8–10% of newborns with asymptomatic congenital cytomegalovirus (cCMV) infection develop sensorineural hearing loss (SNHL). However, the relationship between CMV load, SNHL and central nervous system (CNS) damage in cCMV infection remains unclear. This study aimed to examine the relationship between urinary CMV load, SNHL and CNS damage in newborns with cCMV infection.Study designThe study included 23 368 newborns from two maternity hospitals in Saitama Prefecture, Japan. Urine screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 29 publications
2
47
2
3
Order By: Relevance
“…a Sex from one case could not be determined from CMV-negative group. The 5.8% prevalence of congenital CMV infection found in our study from an urban birth cohort in Indonesia is higher compared to other newborn screening studies in Finland (0.2%) (Puhakka et al, 2018), Japan (0.3%) (Yamaguchi et al, 2017), Iran (0.5%) (Karimian et al, 2016), Panama (0.6%) (Estripeaut et al, 2007), China (0.7%) (Wang et al, 2017), Brazil (1.1%) (Mussi-Pinhata et al, 2009), India (2.1%) (Dar et al, 2008), and Nigeria (3.8%) (Olusanya et al, 2015), but similar to those observed in a peri-urban birth cohort in Gambia (5.4%) (van der Sande et al, 2007) and in a highrisk population in China (6.1%) (Zhang et al, 2007). Although maternal CMV immune status was not assessed in our study, an earlier report on healthy female blood donors has documented a 97.7% CMV seroprevalence in metropolitan Jakarta (Noviar et al, 2017).…”
Section: Discussioncontrasting
confidence: 84%
“…a Sex from one case could not be determined from CMV-negative group. The 5.8% prevalence of congenital CMV infection found in our study from an urban birth cohort in Indonesia is higher compared to other newborn screening studies in Finland (0.2%) (Puhakka et al, 2018), Japan (0.3%) (Yamaguchi et al, 2017), Iran (0.5%) (Karimian et al, 2016), Panama (0.6%) (Estripeaut et al, 2007), China (0.7%) (Wang et al, 2017), Brazil (1.1%) (Mussi-Pinhata et al, 2009), India (2.1%) (Dar et al, 2008), and Nigeria (3.8%) (Olusanya et al, 2015), but similar to those observed in a peri-urban birth cohort in Gambia (5.4%) (van der Sande et al, 2007) and in a highrisk population in China (6.1%) (Zhang et al, 2007). Although maternal CMV immune status was not assessed in our study, an earlier report on healthy female blood donors has documented a 97.7% CMV seroprevalence in metropolitan Jakarta (Noviar et al, 2017).…”
Section: Discussioncontrasting
confidence: 84%
“…Blood collection is inconvenient and painful for neonates, while urine and BM samples are collected more easily; therefore, urine and BM CMV‐DNA tests are recommended for primary screening of neonates with a CMV infection. Moreover, CMV intermittently releases toxins, and CMV samples not in the toxin‐releasing state will not conform to the clinical diagnosis; therefore, repeated, continuous, and multiple tests are suggested to improve the detection rate of CMV infection …”
Section: Discussionmentioning
confidence: 99%
“…Congenital CMV (cCMV) infection increases a child's risk for long-term health problems including hearing loss, and newborn screening for cCMV has been advocated [32]. The mean CMV DNA copy number in newborns with cCMV was 1790 copies/µ L and it was much higher in those newborns that had both sensorineural hearing loss and cCMV [33]. Using a prior cartridge and instrument-based heater design, we have shown feasibility of CMV amplification in a DMF system using saliva samples [34].…”
Section: S Per Cycle)mentioning
confidence: 99%